The Future of Collaborative Human-Artificial Intelligence Decision-Making for Mission Planning - Kase, Sue E.; Hung, Chou P.; Krayzman, Tomer; Hare, James Z.; Rinderspacher, B. Christopher; Su, Simon M. (Frontiers in Psychology, 2022)
In an increasingly complex military operating environment, next generation wargaming platforms can reduce risk, decrease operating costs, and improve overall outcomes. Novel Artificial Intelligence (AI) enabled wargaming approaches, based on software platforms with multimodal interaction and visualization capacity, are essential to provide the decision-making flexibility and adaptability required to meet current and emerging realities of warfighting. We highlight three areas of development for future warfighter machine interfaces: AI-directed decisional guidance, computationally-informed decision-making, and realistic representations of decision spaces. Progress in these areas will enable development of effective human-AI collaborative decision-making, to meet the increasing scale and complexity of today’s battlespace.